2001
DOI: 10.1109/23.983199
|View full text |Cite
|
Sign up to set email alerts
|

Radiation effects on floating-gate memory cells

Abstract: We have addressed the problem of threshold voltage ( TH ) variation in flash memory cells after heavy-ion irradiation by using specially designed array structures and test instruments.After irradiation, low TH tails appear in TH distributions, growing with ion linear energy transfer (LET) and fluence. In particular, high LET ions, such as iodine used in this paper, can produce a bit flip. Since the existing models cannot account for large charge losses from the floating gate, we propose a new mechanism, based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(30 citation statements)
references
References 25 publications
3
27
0
Order By: Relevance
“…By using specially designed instrumentation and devices, we have recently shown that FG charge loss upon heavy ion irradiation is not negligible [11], [12], even when it does not lead to a read error at the circuit output. The charge loss subsequent to a single heavy ion strike appears to be due to two parallel mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…By using specially designed instrumentation and devices, we have recently shown that FG charge loss upon heavy ion irradiation is not negligible [11], [12], even when it does not lead to a read error at the circuit output. The charge loss subsequent to a single heavy ion strike appears to be due to two parallel mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, concern about the TID effect has not been limited to just aerospace applications. In disaster robotics, for example, most of the onboard electronic devices, including flash memory and image sensors, need to be protected from a highly radioactive source to ensure a long and reliable mission after an accident at a nuclear power plant has occurred [5]- [7]. Various hardening methods have been attempted to improve device reliability against the TID effect.…”
mentioning
confidence: 99%
“…The mechanisms proposed to explain soft errors in the floating gate are connected with the phenomena of charge loss from the floating gate due to a transient conductive path across the tunnel oxide as well as charge trapping in the tunnel oxide [18,[23][24][25]. The heavy ion Fig.…”
Section: Fig 2(b)mentioning
confidence: 99%